Sociolinguistics. An epistemic and political introduction - Rodríguez-Iglesias, Ígor (Boletín de Filología, 2021)
In this document I present an overview of the sociolinguistics around its foundation. Specifically, I study the social conditions of sociolinguistic knowledge production, that is, the social condition of possibility through which a set of studies dedicated to discursive interaction emerges. Thus, I inquire into the interest in the social variables involved in the specific use of certain linguistic elements and in interpersonal and intergroup communication.